K-1 Yongquan & Talahridaya points: A key to change the course of cardiopulmonary resuscitation (CPR) rescues - Adrián Ángel Inchauspe; Gabriela Roxana Saidman (Journal of Acute Disease)
Thirty-seven years have passed since the first K-1 resuscitation maneuver implementation next to both basic and advanced CPR failure and Prof. Inchauspe has consistently continued such unique research recovering impending death situation victims in the most varied scenarios. After a dozen publications on the issue –mostly in World Journal of Critical Care Medicine and Hainan University Medical Editorial in China, the number of rescues increased to more than 195 cases. Having been contacted by experts in Ayurvedic medicine from India, the authors made a comparative analysis between said K-1 Yongquan and the Talahridaya points, and realized that not only are they located at the very same place for stimulation, but they are also integrated in the Reconciliation Vessel, a new Marvelous meridian discovered by Prof. Inchauspe within the Ancient Chinese classics. The following paper will show a statistical analysis made by Prof. Inchauspe and Dr. Saidman about the possible future impact that would result from the inclusion of the aforementioned maneuver in life support protocols.